2022
DOI: 10.1097/sap.0000000000003165
|View full text |Cite
|
Sign up to set email alerts
|

Complication Profile of Total Submuscular Versus Prepectoral Tissue Expander Placement

Abstract: BackgroundWe sought to compare the safety profile of prepectoral breast reconstruction with total submuscular tissue expander reconstruction, previously our standard. Primary outcomes of interest in this retrospective cohort study were incidence of infection, hematoma, seroma, mastectomy flap necrosis, and reconstruction loss.MethodsTotal submuscular and prepectoral with acellular dermal matrix reconstructions consecutively performed by a single surgeon (P.D.S.) between January 1, 2016, and December 31, 2019, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Although their study did not find as high a rate of explantation, this is possibly attributable to their prepectoral cohort having a shorter average follow-up time. 28 Similar to a study by Plachinski et al, 30 our study found an increased risk of seroma formation in patients with prepectoral reconstruction as compared with submuscular reconstructions, and at a similar rate of roughly 20%. A recent article by Bekisz et al 33 also found that patients with prepectoral reconstruction experienced higher rates of seroma and explantation compared with patients with total submuscular reconstruction; the current study builds upon this understanding by using a larger cohort and matched populations.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Although their study did not find as high a rate of explantation, this is possibly attributable to their prepectoral cohort having a shorter average follow-up time. 28 Similar to a study by Plachinski et al, 30 our study found an increased risk of seroma formation in patients with prepectoral reconstruction as compared with submuscular reconstructions, and at a similar rate of roughly 20%. A recent article by Bekisz et al 33 also found that patients with prepectoral reconstruction experienced higher rates of seroma and explantation compared with patients with total submuscular reconstruction; the current study builds upon this understanding by using a larger cohort and matched populations.…”
Section: Discussionsupporting
confidence: 89%
“…32 The complication profile of prepectoral reconstructions agrees with some existing literature. Soni et al 28 similarly found a greater rate of SSIs in prepectoral reconstructions compared with total submuscular reconstructions. Although their study did not find as high a rate of explantation, this is possibly attributable to their prepectoral cohort having a shorter average follow-up time.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations